"Rolling" phenomenon in twin screw granulation with controlled-release excipients. (March 2015) - Thompson, M. R.; O'Donnell, K. P.
Abstract The developed knowledge regarding use of twin screw granulators for continuous wet granulation has been primarily limited to immediate release formulations in the literature. The present study highlights an issue previously unreported for wet granulation with twin screw extruders when using formulations containing controlled-release (CR) excipients. Long (3–10 mm), twisted noodle-like granules can be produced in the presence of these excipients that are difficult to control and are anticipated to create complications in downstream unit operations to the granulator. Working with two different CR excipients, METHOCEL™ K4M and Kollidon® SR, each blended at different ratios with a mixture of 80% α-lactose monohydrate/20% microcrystalline cellulose, these unique particles were found to be produced in the conveying elements of the extruder, arising from a rolling action at the top of the screw flights. The CR excipients adhesively strengthen the wetted mass, forming this undesired granule shape such that they persisted to the exit of the machine; the shape appeared most strongly affected by screw speed, producing particles of higher aspect ratio as speed was increased. Adjusting the concentration of these CR excipients in the formulation, the flow rate or the type of compression element used in the screws proved ineffective in controlling the problem. Rather, a re-design of the extruder screws was required to prevent generation of these extended-form granules.